BILINGUAL EDUCATION PROGRAM: TEACHERS’ AND STUDENTS’ PERCEPTION AND ITS CALLENGES IN PESANTREN CONTEXT - Khodaifi Khodaifi (Graduate Program, University of Islam Malang, 2021)
Bilingual education program is supposed to be one of programs that becomes solution for student whose difficulties in foreign language, even it is believed to help future career of students therefore, Pesantren being famous with Islamic curriculum implement bilingual education program. This study investigates teachers and student’s perception along with the challenges of bilingual education in Pesantren context. This study employed descriptive qualitative which interview used as primary tool to collect data. The findings reveal that both teachers and students have positive perception toward bilingual education for some reasons however, there are some challenges encountered such as having difficulties to find appropriate bilingual model, different motivation students have and time management due to another program existed in Pesantren.